CONCENTRATIONS OF IMMUNOREGULATORY PROTEINS AND SOME CYTOKINES IN BLOOD OF WOMEN DURING MENOPAUSAL THERAPY - V. N. Zorina; O. V. Isakova; R. M. Zorina; L. G. Bazhenova; N. A. Zorin (Медицинская иммунология, 2016)
It has been shown that the influence of hormonal and non-hormonal therapy of menopausal syndrome upon immune profile may be variable, and the results of appropriate studies may be often contradictory. The aim of this work was to investigate the influence of hormonal and non-hormonal therapy in menopausal syndrome upon serum levels of some immunoregulatory proteins, i.e., alpha2-macroglobulin (a2-MG), pregnancy-associated alpha 2-glycoprotein (PAG), contents of some related cytokines (IL-6, IL-8, TNFα, IFNγ, IL-2) as well as VEGF amounts. Administration of menopausal hormone treatment and nonhormonal therapy was associated with reduced IL-6 levels in serum, regardless of treatment duration, or type of drug applied. We have found a statistically significant decrease of IL-8 serum levels in the course of dynamic monitoring in the women taking a menopausal hormone preparation containing 1 mg of 17β-estradiol and 5 mg dydrogesterone, and a non-hormonal drug containing genistein (60 mg) for 3-6 months. The levels of VEGF demonstrated high individual variability during therapy of menopausal syndrome. Serum concentrations of immunoregulatory a2-MG were stable in climacteric syndrome, and did not differ from normal values. However, the content of PAG, a known immunosuppressive protein, was increased 3-4 times in serum of 33-50% of the women receiving menopausal hormonal therapy, regardless of progestogen dose (5 or 10 mg dydrogesterone), and duration of its use. These findings suggest a need for individualized drug selection in order to minimize a risk of immunodeficiency conditions in the patients receiving hormone therapy of menopausal syndrome.